A Fast and Rigorously Parallel Surface Voxelization Technique for GPU-Accelerated CFD Simulations (Communications in Computational Physics, 2018)
This paper presents a fast surface voxelization technique for the mappingof tessellated triangular surface meshes to uniform and structured grids that providea basis for CFD simulations with the lattice Boltzmann method (LBM). The core algorithmis optimized for massively parallel execution on graphics processing units(GPUs) and is based on a unique dissection of the inner body shell. This unique definitionnecessitates a topology based neighbor search as a preprocessing step, but also enablesparallel implementation. More specifically, normal vectors of adjacent triangulartessellations are used to construct half-angles that clearly separate the per-triangle regions.For each triangle, the grid nodes inside the axis-aligned bounding box (AABB)are tested for their distance to the triangle in question and for certain well-definedrelative angles. The performance of the presented grid generation procedure is superiorto the performance of the GPU-accelerated flow field computations per timestep which allows efficient fluid-structure interaction simulations, without noticeableperformance loss due to the dynamic grid update.